1993
DOI: 10.1152/jappl.1993.75.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary diffusing capacity, capillary blood volume, and cardiac output during sustained microgravity

Abstract: We measured pulmonary diffusing capacity (DL), diffusing capacity per unit lung volume, pulmonary capillary blood volume (Vc), membrane diffusing capacity (Dm), pulmonary capillary blood flow or cardiac output (Qc), and cardiac stroke volume (SV) in four subjects exposed to 9 days of microgravity (weightlessness, 0 G). The same subjects were studied standing and supine numerous times preflight and in the week immediately after return from space. DL in microgravity was elevated (28%) compared with preflight sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
107
3
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 0 publications
19
107
3
1
Order By: Relevance
“…However, the longest period of time for which G DL CO data are available is 10 days (50); whether an elevated DL CO will persist after several weeks or months in G is not presently known. It does not seem unreasonable to speculate that "subclinical" fluid accumulation in the pulmonary interstitial matrix may be reflected in the changes in SBW and MBW observed during steep HDT, and perhaps those observed during G. However, this is not to say that either HDT or spaceflight results in alveolar fluid accumulation (e.g., pulmonary edema), for indeed the evidence to date does not indicate that pulmonary edema occurs in humans during either HDT or spaceflight (42).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the longest period of time for which G DL CO data are available is 10 days (50); whether an elevated DL CO will persist after several weeks or months in G is not presently known. It does not seem unreasonable to speculate that "subclinical" fluid accumulation in the pulmonary interstitial matrix may be reflected in the changes in SBW and MBW observed during steep HDT, and perhaps those observed during G. However, this is not to say that either HDT or spaceflight results in alveolar fluid accumulation (e.g., pulmonary edema), for indeed the evidence to date does not indicate that pulmonary edema occurs in humans during either HDT or spaceflight (42).…”
Section: Discussionmentioning
confidence: 97%
“…However this may not provide a straightforward explanation, because acute changes in body position, e.g., upright to supine, are more generally found to increase DL CO (42,45). However, the acute increases in DL CO appear primarily due to an increase in pulmonary capillary blood volume and to a lesser extent to changes at the membrane level (42,45). Thus it is possible, despite evidence of acute increases in DL CO , that an increase in lung water content, i.e., fluid retention in the pulmonary interstitium, could occur without overt clinical symptoms over the 60 min of steep HDT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the lung receives virtually the entire cardiac output, it provides a useful window into cardiac function, something that has been exploited extensively [43][44][45]. In summary, cardiac output is elevated (compared with standing) by ,35% after 1 day in microgravity due to a large (60-70%) increase in stroke volume and a concomitant bradycardia.…”
Section: Blood Flowmentioning
confidence: 99%
“…2,3 In these studies, blood pressure was not measured. In another study, Fritsch-Yelle et al 4 observed in 12 astronauts over several flights that the mean 24-hour diastolic arterial pressure, but not systolic pressure, was significantly decreased in space by some 5 mm Hg.…”
mentioning
confidence: 99%